Euglossa bembei sp. n. (Hymenoptera: Apidae): a new orchid bee from the Brazilian Atlantic Forest belonging to the Euglossa cybelia Moure, 1968 species group - Nemésio, André (Zootaxa, 2011)
One species of Euglossa, which has been collected in the Atlantic Forest from Pernambuco to São Paulo in low abundance, is here described as a new species, Euglossa bembei sp. n. An updated identification key for the species of Euglossa (Euglossa) occurring in eastern Brazil is provided.